Domino liver transplants: where do we stand after a quarter-century? A US national analysis. Issue 7 (July 2022) - Ahmed, Ola; Vachharajani, Neeta; Chang, Su-Hsin; Park, Yikyung; Khan, Adeel S.; Chapman, William C.; Doyle, M.B.M.
Abstract: Background: Domino liver transplantation (DLT) utilizes a phenotypically normal explant from select recipients as a donor graft in another patient. The procedure is not widely employed and remains restricted to a small number of centers. The purpose of this study was to assess the national profile of DLT in the United States (US) and evaluate current survival outcomes. Methods: The United Network for Organ Sharing (UNOS) database was queried for all liver transplants (LT) between 1996 and 2020. Outcomes of interest were long-term graft and patient survival. Results: Of 181, 976 LTs performed nationally during the study period, 185 (0.1%) were DLTs. Amyloidosis and maple syrup urine disease (MSUD) accounted for 83% of dominoed allografts. Out of 210 explants with amyloidosis, 103 (49%) were dominoed into secondary recipients. Only 50 (22%) of all MSUD explants (n = 227) were dominoed. Graft survival was 79%, 73% and 53% at 3-, 5- and 10-years, respectively, for DLT recipients. Overall patient survival was 83%, 76% and 57% at 3-, 5- and 10-years. Conclusion: Despite excellent long-term survival outcomes, DLT allografts comprise a very small percentage of the liver donor pool. A large proportion of potential DLTs may be unconscionably excluded despite shortages in deceased donor organs.